Proceedings of the Fifth International Forum on Decision Sciences (Uncertainty and Operations Research,, 2018)
The proceedings volume consists of academic papers on decision-making under uncertainty, smart decision, stochastic optimization, management simulation and its applications. It presents some compelling and valuable results on the cutting-edge modeling methods and the practical case studies in the operations management process for power, transportation, and logistics companies.